Analisis Gelombang Elektromagnetik pada Transmisi Jaringan 5G di Indonesia - Rafif Abyakto; Qonita Auliani; Naif Baihaqi; Muhammad Rizki; Diyajeng Luluk Karlina (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Electromagnetic waves in 5G transmission in Indonesia, a cellular network based on electromagnetic waves, which has revolutionized wireless communications. This wireless technology is more advanced than previous wireless technologies (1G, 2G, 3G and 4G). Electromagnetic waves are a type of electromagnetic radiation consisting of electric and magnetic fields moving simultaneously. 5G operates at a higher frequency than previous cellular technologies. The relationship between 5G signals and electromagnetic waves and their impact on signal performance and range. Here we discuss how 5G operates at higher frequency ranges, including millimeter wave (mmWave), which offers very high data speeds and large capacities. 5G technology is a fifth generation wireless communication network that offers faster data speeds, lower latency, and greater connection capacity compared to previous generations. Of particular concern is the impact of the electromagnetic fields (EMF) generated by this technology on the environment and human health. 5G technology uses higher frequencies in the millimeter wave (mmWave) spectrum, reaching 24 to 100 GHz, in addition to low to medium frequencies also used by 4G networks. Research has shown that the electromagnetic field of 5G technology has different properties, such as shorter wavelengths so that the penetration depth into living tissue is smaller.